GOBERNABILIDAD DEMOCRÁTICA EN AMÉRICA CENTRAL: UNA PROPUESTA DE ANÁLISIS PATH DEPENDENCE DE CARÁCTER NEO INSTITUCIONAL A PARTIR DE LA CRÍTICA DE LOS PLANTEAMIENTOS DE J. MAHONEY. EL CASO DE EL SALVADOR ENTRE 1930 Y 1960. - Viales Hurtado, Ronny (2007)
This article describes a theoretical approach of the democratic governability in Central America through a deliberation on Mahoney’s proposal for a path dependence analysis of neo-institutional character. For this purpose, a comparison is made between the theoretical approach and a case study of El Salvador between 1930 and 1960. In this manner, the article visualizes how in Central America, the problems relating to the path that each particular country followed in the construction of their State and Nation should be analyzed from different points of view. The popular interpretation of path dependence proposed by James Mahoney by itself does not quite explain the Central American evolution. In the particular case of El Salvador, the decisions made by the ruling class evidently affected the economic and political situation of the Salvadorans —especially those made during the period of liberal reforms— but by themselves do not elucidate the subsequent outcome. To this end, the article underscores the importance of broaching the problem in terms of a deliberation on the State and Nation, aimed at proposing further studies that will clarify the key aspects of its construction.